2013
DOI: 10.1080/10408398.2012.742863
|View full text |Cite
|
Sign up to set email alerts
|

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values

Abstract: Zinc was selected as a priority micronutrient for EURRECA, because there is significant heterogeneity in the Dietary Reference Values (DRVs) across Europe. In addition, the prevalence of inadequate zinc intakes was thought to be high among all population groups worldwide, and the public health concern is considerable. In accordance with the EURRECA consortium principles and protocols, a series of literature reviews were undertaken in order to develop best practice guidelines for assessing dietary zinc intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 61 publications
(46 reference statements)
1
37
0
Order By: Relevance
“…There are no known genotypes that would affect the estimation of DRVs for zinc. Significant results for altered putative zinc biomarkers in groups of people with differing gene variants have been documented by Lowe et al (2013).…”
Section: Effects Of Genotypementioning
confidence: 99%
See 2 more Smart Citations
“…There are no known genotypes that would affect the estimation of DRVs for zinc. Significant results for altered putative zinc biomarkers in groups of people with differing gene variants have been documented by Lowe et al (2013).…”
Section: Effects Of Genotypementioning
confidence: 99%
“…The eligibility criteria were the following: studies of healthy adults, whole-day isotope studies of true zinc absorption, reporting measurements of TDZ, and total dietary phytate (TDP) and TAZ. No extensive literature search was performed in addition to that performed by the EURopean micronutrient RECommendations Aligned (EURRECA) network on factors affecting zinc bioavailability (Lowe et al, 2013); relevant publications were identified through knowledge of the existing work of the small number of investigators in this field of research and ongoing monitoring of the new literature. All the data came from research groups having extensive experience with the application of isotope tracer methods to the study of zinc absorption.…”
Section: Identification Of Studies Data Extraction and Assessment Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronutrient-specific results of the systematic reviews can be found elsewhere in this issue (Cashman and Kiely, 2013;Hoey et al, 2013;Hurst et al, 2013;Lowe et al, 2013;Ristic-Medic et al, 2013). The quantitative methodology underlying these reviews is explained and illustrated in Activities 5, 6 and 7.…”
Section: Factorial Approach and Bioavailabilitymentioning
confidence: 99%
“…Using a similar systematic review methodology to that described above, specifically designed search strategies were tailored for each micronutrient followed by screening and data extraction. Details on the results of the systematic reviews and meta-analysis can be found elsewhere in this issue (Cashman and Kiely, 2013;Hoey et al, 2013;Hurst et al, 2013;Lowe et al, 2013;Ristic-Medic et al, 2013). Further details on the methodological approach to summarising and interpreting the data, and integrating the evidence can be found in Activities 5 and 6 respectively.…”
Section: Factorial Approach and Bioavailabilitymentioning
confidence: 99%